Itaconic acid and its applications for textile, pharma and agro-industrial purposes - Devi, Nisha; Singh, Shubhangi; Manickam, Shivakumar; Cruz-Martins, Natália; Kumar, Vinod; Verma, Rachna; Kumar, Dinesh (MDPI, 2022)
Itaconic acid (IA) is a well-known bio-based monounsaturated organic acid (C5H6O4), with a white color and crystalline structure. It is widely used in the agro-based, plastics, textile, paint and pharmaceutical sectors, owing to its flexible structure, due to the presence of functional groups with covalent double bonds. IA is an alternative to the petrochemicals acrylic and methacrylic acids. Commercial manufacturing of IA using Aspergillus terreus is more economically effective and feasible, and the Department of Energy (DOE) of the United States added IA under the “top 12” organic chemicals in 2004. This review provides an overview on the synthesis of IA and improvement of its yield by mutagenesis and metabolic engineering of Aspergillus and other fungal strains, along with its wide applications for food, pharmaceutical and textile purposes.
Keywords: itaconic acid; metabolic engineering; Aspergillus terreus; market scenario